Risk Factor Analysis of Adverse Effects of Kanamycin and Capreomycin on Kidney Function in Multidrug-Resistant TB Patients - Bambang Subakti Zulkarnain; Syefi Nuraeni Fitriana; Herri Yulimanida (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Multidrug-Resistant TB treatment's high side effects and long duration are barriers to successful TB therapy. Various side effects such as age, gender, body weight, comorbidities, and drug dose can cause severe side effects, including impaired renal function (nephrotoxic). Objectives: This study aimed to analyze the risk factors of side effects of the failure of kanamycin and capreomycin therapy that can cause impaired renal function in Multidrug-Resistant TB patients. Methods: Data were collected retrospectively by searching and recording the medical records of Multidrug-Resistant TB patients at the Multidrug-Resistant TB Polyclinic. There were 183 patients at Dr Soetomo Hospital who met the inclusion criteria. Results: There was a significant relationship between gender in the kanamycin group and the appearance of side effects of renal impairment (p= 0.035). There was no effect of age, comorbid diseases, body weight, and dose of drug administration on the side effects of kanamycin and capreomycin in treating Multidrug-Resistant TB on impaired renal function (nephrotoxic). However, nephrotoxic side effects in elderly patients were more common in the kanamycin group (p=0.001). Conclusion: Gender affects the side effects of kanamycin and capreomycin in treating Multidrug-Resistant TB in nephrotoxic patients.  In addition, stricter supervision of the use of kanamycin in elderly patients (>40 years) to minimize the incidence of side effects of impaired renal function in the treatment of Multidrug-Resistant TB.